2019
DOI: 10.1038/s41598-019-52958-0
|View full text |Cite
|
Sign up to set email alerts
|

A plant biostimulant from the seaweed Ascophyllum nodosum (Sealicit) reduces podshatter and yield loss in oilseed rape through modulation of IND expression

Abstract: The yield of podded crops such as oilseed rape (OSR) is limited by evolutionary adaptations of the plants for more efficient and successful seed dispersal for survival. These plants have evolved dehiscent dry fruits that shatter along a specifically developed junction at carpel margins. A number of strategies such as pod sealants, GMOs and hybrids have been developed to mitigate the impact of pod shatter on crop yield with limited success. Plant biostimulants have been shown to influence plant development. A c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 58 publications
1
18
0
Order By: Relevance
“…These two factors would affect the formation of dehisecnce zone. This provide new direction for the breeding varieties with dehiscence-resistant ( Łangowski et al, 2019 ).…”
Section: Signal Of Silique Dehiscencementioning
confidence: 99%
“…These two factors would affect the formation of dehisecnce zone. This provide new direction for the breeding varieties with dehiscence-resistant ( Łangowski et al, 2019 ).…”
Section: Signal Of Silique Dehiscencementioning
confidence: 99%
“…The brown seaweed Ascophyllum nodosum has long been accepted by growers in the international market to have superior performance as compared to biostimulants made from other seaweeds. Ascophyllum nodosum extract (ANE) biostimulants have been shown to improve plant vigor, increase root development, enhance chlorophyll synthesis, promote earlier flowering, enhance fruit set and uniformity of fruit, reduce pod shatter, delay senescence, and enhance tolerance to abiotic stress ( Sangha et al, 2014 ; Łangowski et al, 2019 ; Shukla et al, 2019 ). The impact of processing of the A. nodosum raw material on an ANE biostimulant product is also known to affect compositional and bioactivity-related parameters ( Goñi et al, 2016 , 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…In order to assess whether Sealicit TM had any impacts on soybean pod growth and development, as reported previously for Arabidopsis and WOSR ( Łangowski et al, 2019 ), the average fresh seed weight per pod and pod length were measured in SS and SR varieties. A two-way ANOVA revealed that Sealicit TM had a significant effect on the average fresh seed weight per pod ( p = 0.024) ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Plant biostimulants, especially those extracted from the brown alga Ascophyllum nodosum , have been reported to deliver a number of benefits to plants/crops ( Craigie, 2011 ; Vera et al, 2011 ; Sharma et al, 2013 ; Ali et al, 2016 ; Goñi et al, 2016 , 2018 ; Shukla et al, 2018 , 2019 ; Carmody et al, 2020 ). Previously, we reported the efficacy of a specialty A. nodosum extract (ANE) biostimulant, namely, Sealicit TM , and explored the mode of action (MOA) in reducing pod dehiscence in A. thaliana and winter oilseed rape (WOSR) ( Łangowski et al, 2019 ). Sealicit TM is a novel ANE containing PSI-759 biomolecule complex, produced using a targeted plant signal induction (PSI) approach to formulation development.…”
Section: Introductionmentioning
confidence: 99%